Peran Traditional Markets dan Street Food Vendor Terhadap Pariwisata Kota Bukittinggi - Hardi Yakup; Lingga Yuliana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The purpose of this study is to examine how Bukittinggi City's traditional market and street food vendors affect tourism. This research is a descriptive qualitative study. Tourists who are in Bukittinggi City are the respondents. Primary data is used by the data source. Interviews with visitors to Bukittinggi City performed in April 2025 provided the primary data. The study's findings suggest that Bukittinggi City's traditional market and street food vendors have an impact on tourism. The study's management implications include the need for the Bukittinggi City Council to respond to issues pertaining to street food vendors and the traditional market in a flexible manner. The functioning of the street food vendors and traditional market must be regulated by a draft ordinance in order for Bukittinggi City to attract tourists.